2008
DOI: 10.1074/jbc.m705872200
|View full text |Cite
|
Sign up to set email alerts
|

Domain and Functional Analysis of a Novel Platelet-Endothelial Cell Surface Protein, SCUBE1

Abstract: SCUBE1 (signal peptide-CUB-EGF domain-containing protein 1) is a novel, secreted, cell surface glycoprotein expressed during early embryogenesis and found in platelet and endothelial cells. This protein is composed of an N-terminal signal peptide sequence followed by nine tandemly arranged epidermal growth factor (EGF)-like repeats, a spacer region, three cysteine-rich repeat motifs, and one CUB domain at the C terminus. However, little is known about its domain and biological function. Here, we generated a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
94
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(98 citation statements)
references
References 35 publications
3
94
1
Order By: Relevance
“…Neto2 is a complement C1r/C1s, Uegf, Bmp1 (CUB) domain-containing transmembrane protein abundantly expressed in neurons (12), which is important for proper neurological function (13). CUB domains are evolutionarily conserved protein domains (14) that participate in protein-protein interactions (15,16). In the present study, we performed an unbiased proteomic screen and discovered that Neto2 interacts with KCC2.…”
mentioning
confidence: 99%
“…Neto2 is a complement C1r/C1s, Uegf, Bmp1 (CUB) domain-containing transmembrane protein abundantly expressed in neurons (12), which is important for proper neurological function (13). CUB domains are evolutionarily conserved protein domains (14) that participate in protein-protein interactions (15,16). In the present study, we performed an unbiased proteomic screen and discovered that Neto2 interacts with KCC2.…”
mentioning
confidence: 99%
“…Because of the large and complex genomic structure of the mouse Scube1 gene, designing a targeting strategy for generating a null allele is difficult. Indeed, our previous targeting study disrupted only the COOH-terminal CUB domain of mouse Scube1 (mutant scube1 ⌬cub allele), which resulted in brain malformation and perinatal lethality (34). Although this gene-targeting study clearly demonstrated the role of Scube1 during early stages of central nervous system development, its function in primitive hematopoiesis was not obvious and not thoroughly examined (34).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, our previous targeting study disrupted only the COOH-terminal CUB domain of mouse Scube1 (mutant scube1 ⌬cub allele), which resulted in brain malformation and perinatal lethality (34). Although this gene-targeting study clearly demonstrated the role of Scube1 during early stages of central nervous system development, its function in primitive hematopoiesis was not obvious and not thoroughly examined (34). Given the essential role of Scube1 in primitive hematopoiesis in zebrafish, we are interested in producing a conditional null allele to further explore the biological functions of Scube1 in mammalian hematopoiesis or other developmental processes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations